Anticipating postoperative complications in hepatobiliary surgery: procalcitonine as predictive factor - Zhao, Shouwen; Song, Yuanyuan; Zhang, Le; Shi, Sunan; Li, Jie; Ma, Yuping; Liao, Yong; Zhen, Zhongguang (Frontiers in Surgery, 2025)
Background and aimsFew studies have indicated that procalcitonin has a potential role in anticipating postoperative complications of hepatic surgery. Here, we focused on validating the relationship between posthepatectomy and serum procalcitonin as short-term prognostic factors.MethodsData from 52 patients who underwent hepatectomy (partial) due to hepatocellular carcinoma from June 2018 to July 2023 were enrolled to evaluate the risk factors related to post-hepatectomy complications, especially post-hepatectomy liver failure and 30-day survival.Results52 patients were included in the study, and their data was analyzed for PCT. 21 showed raised PCT (>1 ng/ml). Results showed a significant association of PCT with post-hepatectomy liver failure, and the same is associated with 30-day mortality in ICU-admitted patients.ConclusionElevated PCT levels in patients after hepatic surgery are associated with poor prognosis and could be used as a potential predictive factor.